1990
DOI: 10.1099/00221287-136-6-1109
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis infection of human fallopian tube organ cultures

Abstract: The pathogenic events that precede Chlamydia trachomatis salpingitis in the human fallopian tube have not been fully described. We used a model of human fallopian tubes in organ culture (HFTOC) infected with strain E/UW-5/CX of C. trachomatis to study these events. The model supported sustained C. trachomatis infection as demonstrated by recovery of viable C. trachomatis from medium and tissue over 5-7 d. However, the level of infectivity was low. Maximal infection occurred at 72 h after initial inoculation. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 18 publications
2
38
0
Order By: Relevance
“…This will eventually lead to permanent tubal tissue damage and scaring [114]. Chlamydial infection can affect oviductal smooth muscle and destroy its spontaneous contractile activity which will ultimately result in stasis and retention of the oviduct secretions, hydro/ pyosalpinx formation and infertility [115].…”
Section: Smokingmentioning
confidence: 99%
“…This will eventually lead to permanent tubal tissue damage and scaring [114]. Chlamydial infection can affect oviductal smooth muscle and destroy its spontaneous contractile activity which will ultimately result in stasis and retention of the oviduct secretions, hydro/ pyosalpinx formation and infertility [115].…”
Section: Smokingmentioning
confidence: 99%
“…Fallopian tube tissue was obtained from women undergoing elective hysterectomies as described previously (36). The fallopian tubes were cleaned of adventitial tissue, cut into 2 mm 2 square pieces and incubated overnight in MEM/F-12 supplemented with 10% FBS.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Many studies have suggested that most chlamydial disease sequelae are caused by immunopathological reaction (Cooper et al, 1990;Hutchinson et al, 1979;Patton, 1985;Quinn et al, 1992). From the public health perspective, the most troublesome aspect of chlamydial infection is not the infection per se, rather, it is the immunopathological responses that cause major health problems including blindness, infertility, and ectopic pregnancy.…”
Section: Introductionmentioning
confidence: 99%